2012
DOI: 10.1016/j.physb.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric resonance in Rochelle salt: The contribution of diagonal strains

Abstract: Within the framework of two-sublattice Mitsui model with taking into account the shear strain ε 4 and the diagonal strains ε 2 and ε 3 , a dynamic dielectric response of Rochelle salt X-cuts is considered. Experimentally observed phenomena of crystal clamping by high frequency electric field, piezoelectric resonance and microwave dispersion are described. It is shown that the lowest resonant frequency is always associated with the ε 4 shear mode

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Figure 1: Temperature dependences of the lowest resonance frequency of the Rochelle salt X-cut with l y = 1.60 cm, l z = 2.45 cm . Solid line: the present theory with the defect-mediated relaxation, A 0 = 1.1 • 10 −4 , E b = 4.5 • 10 3 V/m, τ 0 = 5.95 • 10 −16 s, W = 0.5 eV; dashed line: the earlier theory[23]. Symbols: experimental points of[9].…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…Figure 1: Temperature dependences of the lowest resonance frequency of the Rochelle salt X-cut with l y = 1.60 cm, l z = 2.45 cm . Solid line: the present theory with the defect-mediated relaxation, A 0 = 1.1 • 10 −4 , E b = 4.5 • 10 3 V/m, τ 0 = 5.95 • 10 −16 s, W = 0.5 eV; dashed line: the earlier theory[23]. Symbols: experimental points of[9].…”
mentioning
confidence: 88%
“…This field gives rise to the shear strain ε 4 at all temperatures, as well as to the diagonal strains ε 1 , ε 2 , ε 3 in the ferroelectric phase. Influence of the in-plane extensional vibrational modes associated with ε 2 and ε 3 on the dynamic permittivity of Rochelle salt X-cuts has been explored in detail in [23]. In particular, it was shown that the extensional modes are excited only in the ferroelectric phase (as follows from the system symmetry), and that the lowest piezoelectric resonance frequency is always associated with the shear mode.…”
Section: Dynamic Linear and Non-linear Susceptibilities Of Rochelle Saltmentioning
confidence: 99%
See 3 more Smart Citations